2019
DOI: 10.5539/ijps.v11n2p73
|View full text |Cite
|
Sign up to set email alerts
|

Figurative Language Comprehension in Schizophrenia and Its Neural Basis

Abstract: Schizophrenia is a kind of serious mental disease, which may cause major impairment in patients’ social-cognitive ability. It has been found that pragmatic ability in schizophrenic patients is often impaired, especially for figurative language comprehension. Figurative language refers to irony, metaphor, idiom and the like. People with schizophrenia tend to interpret figurative language as its literal meaning, which is called schizophrenic concretism. By reviewing extant literature, we found that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Extensive research has been conducted to reveal the neural resources and brain networks responsible for language comprehension, especially between literal and figurative language in healthy [ 5 ] and clinical population [ 6 ]. Underlying metaphor comprehension is the uniquely human capacity to resolve ambiguity in phrases such as “family is a harbour,” where conceptual mapping [ 7 , 8 ] is needed between the target “family” and its source, “harbour.” The methods related to the investigation of metaphor comprehension have a wide range of applications, reaching from the diagnoses of learning deficits [ 9 ], untangling impairment due to psychosis [ 10 ], to the study of creativity [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Extensive research has been conducted to reveal the neural resources and brain networks responsible for language comprehension, especially between literal and figurative language in healthy [ 5 ] and clinical population [ 6 ]. Underlying metaphor comprehension is the uniquely human capacity to resolve ambiguity in phrases such as “family is a harbour,” where conceptual mapping [ 7 , 8 ] is needed between the target “family” and its source, “harbour.” The methods related to the investigation of metaphor comprehension have a wide range of applications, reaching from the diagnoses of learning deficits [ 9 ], untangling impairment due to psychosis [ 10 ], to the study of creativity [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the neural basis of figurative language comprehension in schizophrenia, many studies have found that schizophrenic patients have distinct language lateralization compared with normal people; this abnormal lateralization is believed to be associated to symptoms presented in this disorder 13 .…”
Section: Introductionmentioning
confidence: 99%